2014
DOI: 10.4162/nrp.2014.8.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Communicating clinical research to reduce cancer risk through diet: Walnuts as a case example

Abstract: Inflammation is one mechanism through which cancer is initiated and progresses, and is implicated in the etiology of other conditions that affect cancer risk and prognosis, such as type 2 diabetes, cardiovascular disease, and visceral obesity. Emerging human evidence, primarily epidemiological, suggests that walnuts impact risk of these chronic diseases via inflammation. The published literature documents associations between walnut consumption and reduced risk of cancer, and mortality from cancer, diabetes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Although the major fatty acid in walnuts is linoleic acid (n-6), the content of linolenic acid (n-3), is substantial [6]. Walnuts contain higher amounts of linolenic acid (n-3) than any other nuts (almonds, hazelnuts, chestnuts) [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the major fatty acid in walnuts is linoleic acid (n-6), the content of linolenic acid (n-3), is substantial [6]. Walnuts contain higher amounts of linolenic acid (n-3) than any other nuts (almonds, hazelnuts, chestnuts) [38].…”
Section: Discussionmentioning
confidence: 99%
“…hazelnuts and almonds) [3,4]. The ratio of ALA to linoleic acid is high among all the tree nuts [5] meaning that walnuts have a beneficial n-6/n-3 ratio [6]. Given the cultural acceptability of walnuts as a traditional food, walnuts are seen as an excellent candidate for improving n-3 fatty acid intake [7].…”
Section: Introductionmentioning
confidence: 99%
“…Data from PREDIMED and other studies indicated an association between walnut consumption and reduced risk of cancer and mortality particularly in the context of the MD. Numerous components of walnuts, including α-linolenic acid (ALA), ellagitannins, γ-tocopherol, melatonin, β-sisterol and fiber may counter inflammation-related cancer mechanisms [ 140 ]. In particular, one-year of the MD supplemented with either extra virgin olive oil or mixed nuts (walnuts, almonds, and hazelnuts) versus a low fat diet decreased intercellular adhesion molecule-1 (ICAM-1), IL-6, TNFR60, and TNFR80 levels in adults [ 141 ].…”
Section: The Mediterranean Dietmentioning
confidence: 99%
“…The walnut is rising in popularity for its beneficial effects to the brain, the blood lipid profile, cardiovascular disease, diabetes and so on 3 , 4 . For instance, walnuts can increase in human inferential verbal reasoning 5 and have been associated with a reduced risk for cancer 6 , 7 . In China, there are a large number of walnuts to export every year 8 .…”
Section: Introductionmentioning
confidence: 99%